A framework for mitigating excessive transportation in the context of manufacturing localization - KILIÇ, HÜSEYİN SELÇUK (My University, 2022)
IEEEWhile the zeitgeist of today prescribes localization as a key to eliminate the excessive transportation for manufacturing firms, firm-level practical and workable guidelines that go beyond maxims are scant. Laden with analytical methods, this paper offers a phronetic, customizable framework based on Lean Six Sigma (LSS). The framework mimics Define-Measure-Analyze-Improve-Control (DMAIC) process. The early phases of the framework, ex-ante, prescribe the use of a variety tools and techniques from Lean Six sigma (LSS) and employ fuzzy analytic hierarchy process (FAHP) to extract the vital few root-causes that may impede localization. The latter phases suggest the use of design of experiments (DOE) to evaluate the root-causes, ex-post. The paper outlines a clear and established procedure and demonstrates each analytical phase using evidence from a two-year real-world application in steel industry.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Bilgisayar Bilimleri; Algoritmalar; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Computer Sciences; algorithms; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MATEMATİK, UYGULAMALI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; MATHEMATICS, APPLIED; Fizik Bilimleri; Hesaplamalı Teori ve Matematik; Yapay Zeka; Uygulamalı matematik; Control and Systems Engineering; Physical Sciences; Computational Theory and Mathematics; Artificial Intelligence; Applied Mathematics; AHP; Companies; Costs; fuzzy logic; inshoring; localization; Location awareness; Manufacturing; offshoring; Outsourcing; reshoring; Sustainable development; Transportation; transportation